Perceived stress and its psychosocial and clinical correlates among patients with pulmonary tuberculosis: A cross-sectional study - Mustefa Mohammedhussein; Aman Dule; Worknesh Tessema; Almaz Mamaru; Arefayne Alenko (Indian Journal of Psychiatry)
Background: Although various psychosocial consequences of pulmonary tuberculosis (PTB) have been thoroughly evaluated, perceived stress has not been well studied. Aim: This study assessed perceived stress and its psychosocial and clinical correlates. Methods: An institution-based cross-sectional study was conducted among 410 PTB patients. Data were analyzed by Statistical Package for the Social Sciences (SPSS) v23. Independent sample t-test and Pearson correlation were used to test the association between perceived stress and other variables. Assumptions of linear regression were checked. Multiple regression analysis was done to identify statistically significant association at P < 0.05. Results: Anxiety, perceived social support, and stigma were found to have significant association with perceived stress in multiple regression analysis. Perceived social support and duration of treatment were negatively significantly associated with perceived stress. Patients with PTB had high perceived stress, and moderate to strong significant correlation was observed among variables. Conclusion: Interventions tailored at addressing various psychosocial aspects of tuberculosis (TB) are needed.